Does defending help? The role of peer defending in reducing victimization and enhancing victims’ psychological adjustment - Laninga-Wijnen, Lydia; Yanagida, Takuya; Garandeau, Claire F. (American Psychological Association (APA), 2026)
Although many antibullying programs encourage students to defend victimized peers, there is little empirical evidence that being defended actually helps victims of bullying by diminishing victimization and improving their psychological adjustment (i.e., self-esteem, depressive symptoms, and loneliness) over time. Therefore, the current longitudinal study examines whether defended victims experience a stronger within-person decrease in victimization and psychological problems over time than nondefended victims, while distinguishing between bully- and victim-oriented defending and evaluating the effect of the number of defenders. Among n = 6,470 Finnish fourth- to ninth-grade students, surveys were administered in September/October (T1), January (T2), and April. A total of n = 1,493 and n = 1,303 students indicated that they were victimized by their peers at T1 and T2, respectively; 75.1% of the T1 victims and 70.6% of the T2 victims reported being defended. Descriptive statistics indicated that defended victims were less frequently victimized and experienced fewer psychological problems than nondefended victims at most time points (cross-sectional associations). However, longitudinal findings consistently indicated that defended victims did not experience stronger within-person decreases in victimization and psychological problems than nondefended victims. No significant interaction effects with gender and age were detected. Thus, the benefits of being defended for victims of bullying may be more limited than often assumed, at least in the longer term.